Association of γ-Secretase with Lipid Rafts in Post-Golgi and Endosome Membranes - Vetrivel, Kulandaivelu S.; Cheng, Haipeng; Lin, William; Sakurai, Takashi; Li, Tong; Nukina, Nobuyuki; Wong, Philip C.; Xu, Huaxi; Thinakaran, Gopal (The Journal of biological chemistry, 2004)
Alzheimer's disease-associated beta-amyloid peptides (Abeta) are generated by the sequential proteolytic processing of amyloid precursor protein (APP) by beta- and gamma-secretases. There is growing evidence that cholesterol- and sphingolipid-rich membrane microdomains are involved in regulating trafficking and processing of APP. BACE1, the major beta-secretase in neurons is a palmitoylated transmembrane protein that resides in lipid rafts. A subset of APP is subject to amyloidogenic processing by BACE1 in lipid rafts, and this process depends on the integrity of lipid rafts. Here we describe the association of all four components of the gamma-secretase complex, namely presenilin 1 (PS1)-derived fragments, mature nicastrin, APH-1, and PEN-2, with cholesterol-rich detergent insoluble membrane (DIM) domains of non-neuronal cells and neurons that fulfill the criteria of lipid rafts. In PS1(-/-)/PS2(-/-) and NCT(-/-) fibroblasts, gamma-secretase components that still remain fail to become detergent-resistant, suggesting that raft association requires gamma-secretase complex assembly. Biochemical evidence shows that subunits of the gamma-secretase complex and three TGN/endosome-resident SNAREs cofractionate in sucrose density gradients, and show similar solubility or insolubility characteristics in distinct non-ionic and zwitterionic detergents, indicative of their co-residence in membrane microdomains with similar protein-lipid composition. This notion is confirmed using magnetic immunoisolation of PS1- or syntaxin 6-positive membrane patches from a mixture of membranes with similar buoyant densities following Lubrol WX extraction or sonication, and gradient centrifugation. These findings are consistent with the localization of gamma-secretase in lipid raft microdomains of post-Golgi and endosomes, organelles previously implicated in amyloidogenic processing of APP.